2019
DOI: 10.1002/ehf2.12394
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary experience with the multisensor HeartLogic algorithm for heart failure monitoring: a retrospective case series report

Abstract: Aims In the Multisensor Chronic Evaluation in Ambulatory Heart Failure Patients study, a novel algorithm for heart failure (HF) monitoring was implemented. The HeartLogic (Boston Scientific) index combines data from multiple implantable cardioverter defibrillator (ICD)‐based sensors and has proved to be a sensitive and timely predictor of impending HF decompensation. The remote monitoring of HF patients by means of HeartLogic has never been described in clinical practice. We report post‐implantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 12 publications
4
46
1
Order By: Relevance
“…This seems to suggest that in this case, the clinical event had a cardiac origin. As previously described, 12,13 the HeartLogic alert diagnosed an impending HF event before signs or symptoms occurred, it early detected discontinuation of the HF therapy and allowed to reestablish it promptly.…”
Section: Discussionmentioning
confidence: 89%
“…This seems to suggest that in this case, the clinical event had a cardiac origin. As previously described, 12,13 the HeartLogic alert diagnosed an impending HF event before signs or symptoms occurred, it early detected discontinuation of the HF therapy and allowed to reestablish it promptly.…”
Section: Discussionmentioning
confidence: 89%
“…The authors concluded that this algorithm might be able to detect clinical worsening in patients with HF early before a critical clinical deterioration. 28 When comparing patients with HF events versus patients without HF events, our results show that patients with HF events had a significantly lower EF at the end of WCD use compared with patients without HF events (31 ± 10% vs. 35% ± 10%; P = 0.005), and patients with HF events more often reported symptoms related to decompensated HF (P < 0.001). In our CABs and HR algorithm, we used a dual threshold strategy to stratify patients into low-risk and high-risk group categories for an HF event.…”
Section: Discussionmentioning
confidence: 76%
“…Each of the high‐risk alerts of the HeartLogic algorithm had contributions from changes in S1 and/or S3 amplitudes providing additional evidence that CABs are useful in early detection of an impending HF event. The authors concluded that this algorithm might be able to detect clinical worsening in patients with HF early before a critical clinical deterioration 28 …”
Section: Discussionmentioning
confidence: 99%
“…Finally, the HeartLogic ™ algorithm combines novel sensor parameters such as heart sounds and markers of ventilation, along with other measurements like thoracic impedance, heart rate, and activity into an index for the early detection of worsening HF. 10 Following recent publications on this new and unique feature, [11][12][13][14][15][16] the SMART Registry will provide data on relevant sample size in real-life scenario and may help in evaluating the relationship between sensor data and CRT response.…”
Section: Devices Usedmentioning
confidence: 99%